Infestação diferencial de Eimeria spp. (Apicomplexa: Eimeriidae) em indivíduos de Gracilinanus agilis (Didelphimorphia: Didelphidae) na Estação Ecológica do Panga, Uberlândia-MG: padrões e processos. - Strona, Ana Letícia Sousa (2016)
The aggregation of parasites in certain individuals of the host population is associated with differential exposure and susceptibility, which vary according to sex, body size, reproductive condition, space use behavior (which influences the probability of catches and recaptures in different locations) and environmental factors. Thus, the objective of this study was to evaluate the influence of such factors on the infection of Eimeria spp. (intestinal endoparasite) in Gracilinanus agilis, a semelparous didelphid neotropical marsupial. The collection site was a restricted-sense cerrado fragment at the Panga Ecological Station, MG, between 2011 to 2015. A capture-mark-recapture method was used for the hosts identification and the prevalence and abundance of the parasite were evaluated by means of laboratory fecal analyzes. The abundance and prevalence of Eimeria spp. were associated mainly with the reproductive status of the individuals, with both sexes presenting higher prevalence and high parasitic abundance during the end of the reproductive period, which coincides with the rainy season. Males had more parasites than females during the dry season, when the breeding season begins, in which mating occurs. The hypotheses wasn’t confirmed that the highest abundance on males would be due to their greater spatial displacement. However, the number of recaptures of G. agilis was significantly correlated with the abundance of Eimeria spp. This pattern can be explained by the greater contact of the marsupial with its own feces, which transmit the parasites, as well as by the increased stress caused by the entrapment, that negatively influences the immunological system efficiency. Thus, the presence and abundance of Eimeria spp. during the reproductive period in both sexes seems to be due to behavioral differences that define distinctions in susceptibility to infection rather than host exposure, once we failed to find any correlation between host mobility and Eimeria infection. However, our estimates of G. agilis use of space shoud be viewed with caution, due to the low number of recaptures which could lead to underestimates, and consequently disrupts any existing relationship between these variables.